Empirical Experience and Experimental Evaluation of Open5GCore over Hypervisor and Container. (21st January 2018) - Chang, Hung-Cheng; Qiu, Bo-Jun; Chen, Jyh-Cheng; Tan, Tze-Jie; Ho, Ping-Fan; Chiu, Chen-Hao; Lin, Bao-Shuh Paul
Abstract : One of the most important technologies for future 5G networks is to utilize Network Function Virtualization (NFV) to virtualize the network components. NFV provides flexibility, short time to market, and low cost solution to build network services, which are important features of 5G networks. Although the idea of virtualization is just being applied to cellular networks, it has been used in the community of cloud computing. There are two main virtualization techniques, hypervisor and container. In this paper, we present our practical experience of virtualizing Open5GCore, a commercial product of SDN-enabled Evolved Packet Core (EPC), over hypervisor and container. In addition to describing how to virtualize Open5GCore, we also present the experimental performance evaluation of the systems. Finally, some important lessons learned are provided.